2021
DOI: 10.1093/rpd/ncab080
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Clinical Trials in Medical Imaging System Evaluation and Optimisation

Abstract: Virtual clinical trials (VCTs) can be used to evaluate and optimise medical imaging systems. VCTs are based on computer simulations of human anatomy, imaging modalities and image interpretation. OpenVCT is an open-source framework for conducting VCTs of medical imaging, with a particular focus on breast imaging. The aim of this paper was to evaluate the OpenVCT framework in two tasks involving digital breast tomosynthesis (DBT). First, VCTs were used to perform a detailed comparison of virtual and clinical rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…We have previously shown that voxel-replacement for calcifications results in realistic images. 5,7,9,14 This arises because the attenuation of calcifications is markedly higher than any soft tissue. As a result, the calcifications will always show positive contrast again breast tissue, either adipose, glandular, or carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that voxel-replacement for calcifications results in realistic images. 5,7,9,14 This arises because the attenuation of calcifications is markedly higher than any soft tissue. As a result, the calcifications will always show positive contrast again breast tissue, either adipose, glandular, or carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that voxel‐replacement for calcifications results in realistic images 5,7,9,14 . This arises because the attenuation of calcifications is markedly higher than any soft tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations